The Use of E-Learning in Discovery Learning: Its Influence on Students' Mathematical Disposition and Mathematical Concept Understanding - Sudarman, Sudarman; Rohman, Wahyu; Anggoro, Bambang Sri; Sugiharta, Iip; Suherman, Suherman (Universitas Islam Negeri Raden Intan Lampung, 2022)
E-learning, assisted by Google Classroom, can be used to provide material and discussions. This research aimed to analyze the effect of e-learning on mathematical disposition and mathematical concept understanding using discovery learning. This research was experimental research with a non-equivalent control group design. The population of this research was the eleventh-grade science students (168 students). The sampling technique employed was random cluster sampling. Data collection techniques used were interviews, tests, and questionnaires. The test results showed that students in the experimental class obtained an average score of 71.7, while the control class obtained a score of 62.9. The results of the mathematical disposition questionnaire showed that experimental class students were more active and confident in solving problems. Thus, e-learning using discovery learning can improve mathematical disposition and mathematical concept understanding. It is suggested to the teacher to develop this learning for other materials.